Crises at work economy, climate and pandemic - Williams, Steve (Bristol University Press, 2024)
It is impossible to view the news at present without hearing talk of crisis: the economy, the climate, the pandemic. This book asks how these larger societal issues lead to a crisis with work, making it ever more precarious, unequal and intense. Experts diagnose the nature of the problem and offer a programme for transcending above the crises.